2013
DOI: 10.7150/ijms.6841
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of the Level of Serum Anti-TF, -Tn and -Alpha-Gal IgG to Survival in Gastrointestinal Cancer Patients

Abstract: Objective: To evaluate the relation of the level of serum anti-TF, -Tn and -αGal carbohydrate antibodies to survival in gastrointestinal cancer patients.Methods: The level of anti-TF (Thomsen-Friedenreich antigen), -Tn and -αGal IgG was analysed in the serum of patients with gastric (n = 83) and colorectal (n = 51) cancers in the long-term follow-up, using ELISA with polyacrylamide glycoconjugates. To evaluate overall survival and the risk of death, the Kaplan-Meier method and the Cox proportional hazards mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 38 publications
(49 reference statements)
2
25
0
Order By: Relevance
“…Besides, changes of some parameters, such as IgG/IgM and IgA/IgM ratios and SNA/IgG index, revealed a good diagnostic accuracy at the early stages of colon cancer and can be used as novel diagnostic biomarkers. The anti-TF IgG level was associated with a better survival, which was in accordance with previously reported findings in patients with gastrointestinal or breast cancer [18][19][20][40][41][42]. In order to establish whether the relative proportions of different anti-TF antibody isotypes have diagnostic and/or prognostic value, we attempted to establish the ratio between the levels of TF-specific IgG, IgM and IgA antibodies at different stages of colon cancer.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Besides, changes of some parameters, such as IgG/IgM and IgA/IgM ratios and SNA/IgG index, revealed a good diagnostic accuracy at the early stages of colon cancer and can be used as novel diagnostic biomarkers. The anti-TF IgG level was associated with a better survival, which was in accordance with previously reported findings in patients with gastrointestinal or breast cancer [18][19][20][40][41][42]. In order to establish whether the relative proportions of different anti-TF antibody isotypes have diagnostic and/or prognostic value, we attempted to establish the ratio between the levels of TF-specific IgG, IgM and IgA antibodies at different stages of colon cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Having altered post-translational modifications and/or aberrantly expressed, tumorassociated glycans can trigger an immune response [1,2,10,33]. Naturally occurring antibodies to tumorassociated glycans, including the TF glycotope, were shown to participate in antibodies-mediated tumor defence, and their level was associated with tumor progression, metastases, and patients survival [7,8,[18][19][20]. A common trend towards the decrease of the level of natural anti-TF antibody in serum was found in cancer patients [12,13,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that various Ab glycoforms display different effector functions and determine the activity of antibodies against tumors [ 5 , 39 41 ]. Previous studies have demonstrated that naturally occurring antibodies to tumor associated glycans are involved in natural tumor immunity, being associated with tumor progression and cancer patients survival [ 18 , 26 , 42 , 43 ]. Natural anti-TF antibodies (Abs) of different isotypes (IgG, IgM, and IgA) are present in each individual thus making these antibodies a convenient target for analysis, in contrast to tumor-derived products that may be detected in a minority of patients due to their extreme dilution in the circulation and rapid degradation or clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, a decrease in the level of serum TF-specific Abs is usually observed [911, 13]. However, no data still exist on the possible involvement of any particular subset of anti-TF IgG Abs in this decrease.…”
Section: Discussionmentioning
confidence: 99%